야간전담 간호사의 고정근무 방식이 직무몰입과 만족에 미치는 영향 - 방정아; Bang Jeong-a; 정현석; Joung Hyunsuk; 이돈희; Lee Donhee (品質經營學會誌, 2024)
Purpose: This study empirically analyzes the effect of a fixed nightshift schedule on job engagement and job satisfaction Methods: Data was collected from nurses with experience working fixed nightshifts at a tertiary general hospital located in Incheon, South Korea. The research model and hypotheses were examined using SPSS 25.0 and AMOS 25.0. Results: The results of this study are as follows; the perception of fixed nightshift, the perception of compensation/salary and the perception of personal life had positive effects on job engagement, but the perception of interrelatedness of fixed nightshift had not positive effect on job engagement. Job engagement had a positive effect on job satisfaction among nurses on the nightshift. Therefore, the results of the study are significant in that they provide new strategic insights for the effective implementation and use of different fixed-shift systems in healthcare organizations. Conclusion: To ensure nurses' job satisfaction, it is important to ensure autonomy in choosing the type of work and to establish a work system that suits the characteristics of each individual. It is necessary to create an environment in which nurses can immerse themselves in their work through different types of work and appropriate rewards for each. This study provides valuable insights for developing operational strategies to improve working conditions for nurses.